Kematangan Beragama Muallaf di Pakis Aji Jepara: Pengaruh Sikap dan Motif Beragama - Laila, Azzah Nor; Andriyani, Santi; Nafisah, Zahrotun (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the influence of religious motives and attitudes on religious maturity in the group of converts in Pakis Aji, Jepara. The urgency of this research is to prove the influence of religious motives and attitudes on religious maturity. The scientific contribution of this research enriches psychological theory, religious maturity, adds to the treasures related to the form and practice of religious maturity based on the muallaf experience. The research used quantitative methods. The research sample was used random sampling technique. Respondents in this study were 30 Muslim converts in Pakis Aji sub-district. The results showed a significant influence between religious motives and religious maturity with a significance value of 0.00 <0.05 and t count 4.797> t table 2.048, which indicates that religious motives have an important contribution in increasing spiritual maturity. In addition, there is a simultaneous influence between religious motives and attitudes towards religious maturity, as evidenced by a significance value of 0.00 <0.05. Correlation analysis shows that religious motives (X1) and religious attitudes (X2) have a strong relationship with religious maturity (Y), with a correlation coefficient of 0.722. The contribution of religious motives and attitudes variables to religious maturity reached 52.1%, while the remaining 47.9% was influenced by other factors not analyzed in this study. This study confirms that increasing religious maturity in converts depends not only on internal motivation but also on a consistent attitude in practicing religious teachings.